Analisis Faktor-Faktor Yang Berhubungan Dengan Kompetensi Perempuan Dalam Pemanfaatan Pekarangan - Manoppo, Conny Naomi; Amanah, Siti (JURNAL AGRIBISNIS TERPADU, 2018)
Utilization of the home gardens as a source of food diversity optimally and sustainably requires the competence of the owners (women) of the home gardens. The study aims to analyze factors that relate significantly to the technical, managerial and social competencies of women in practicing their home garden to support food diversification. The research was conducted in two regions of North Sulawesi (Minahasa Regency and Bitung City), from March 2015 to December 2015. The respondents were 267 housewifes selected out of 803 women participating on the home gardening intensification programs. Data analysis using descriptive analysis, and Pearson correlation analysis. The results show that technical competence is significantly related to: availability of information, conformity of information, availability of production facilities, social culture, group roles as learning class, production unit and cooperation, extension and perception. Managerial competence is significantly related to nonformal education, information conformity, informant credibility, group roles, extension and perceptions. Social competence is significantly related to formal education, nonformal education, information availability, information conformity, availability of production facilities, group roles, extension and perception (function of the home gardens, food diversification and healthy foods).